Proceeding of the Building Surveying and Technology Undergraduate Conference 2013 (BUSTUC 2013): Honouring the Past, Treasuring the Present, Shaping the Future - HBP, School of Housing Building & Planing (Pusat Pengajian Perumahan, Bangunan & Perancangan (School of Housing, Building & Planning), Universiti Sains Malaysia, 2013)
BUSTUC2013 is the first conference of this kind in which undergraduate students majoring in Building Surveying and Building Technology come forward with a conference paper and present their research findings in this specialized conference. Students undergo no less than fifteen weeks of training in carrying out scientific research and simultaneously choosing their research topics for actual research. Under the guidance of course lecturers and individual research supervisors the undergraduate students embarked on what can be considered their maiden voyage into scientific research activities. This conference event is the manifestation of the effort by not only the students but also their respective supervisors in order to ensure the training and supervision does not go to waste. The conference papers are published according to international and standardized format and for most of the students this will be their first publication to be remembered long into their future. We look forward to work again with all the respected supervisors and their future students; and to carry on the publication annually. We hope, this effort will ensure all graduating students are equipped with the fundamental of scientific research and publication techniques. We would also like to extend our heartfelt appreciation to the contributors of these Proceedings and the presenters at the Building Surveying and Technology Undergraduate Conference 2013 making the event a convention of thought-provoking, innovative ideas and memorable one.